Mediastinal hematoma following thrombolysis for acute pulmonary thromboembolism - Chitra Veluthat; Uma Maheswari Krishnaswamy; Kavitha Venkatnarayan; Priya Ramachandran; Uma Devaraj (Respirology Case Reports, 2023)
Abstract Massive pulmonary thromboembolism (PE) is a cardiorespiratory emergency and can be fatal if left untreated. The recommended treatment for PE in the presence of right ventricular dysfunction and hemodynamic instability is thrombolysis. However, the latter is a double‐edged sword as life‐threatening bleeding manifestations can occur post‐thrombolysis. Timely identification and management of these complications can prevent a catastrophic outcome. We report a case of mediastinal hematoma with new onset hemodynamic compromise following thrombolysis for acute massive pulmonary embolism. Clinico‐radiological features and Point of Care Ultrasound (POCUS) findings helped in the identification of the bleeding site in our case. Despite early diagnosis and timely intervention, the patient succumbed to secondary complications.